Electrochemical characterization and joule heating performance of polyaniline incorporated cotton fabric. (February 2023) - Parvez, Md. Shohan; Rahman, Md. Mustafizur; Samykano, Mahendran; Yeakub Ali, Mohammad
Abstract: Cutting-edge technological advancements have dramatically shifted toward flexible and wearable electronic devices. Intrinsic conductive polymer Polyaniline (PANI) is acting as a protagonist in this sector because of its synergistic optical and electrical properties of both metals and semiconductors. However, PANI applications can be restricted due to their rigid-brittle form, relative conductivity, and specific choice of solvents for processing. Integrating PANI with textile material can provide interesting interactive functionality for wearable electronics applications. This paper investigates the electrochemical characterization and joule heating performance of Polyaniline (PANI) induced cotton fabric by implementing a straightforward in-situ chemical oxidative polymerization. Conductivity augmentation of PANI-induced Cotton fabric is performed using a facile pre-treatment process and by varying dopant concentrations. Optical microscopic imaging, SEM, probe conductivity test, FTIR analysis, cyclic voltammetry, and joule heating performance were performed to justify the findings. The impact of the pretreatment process using NaOH can enhance the conductivity significantly by reducing the surface resistivity to 1.39 kΩ/cm, which showed better performance than fabric coated with Poly (3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT: PSS, 10 Dipping cycles). Additionally, the PANI-treated fabric has a long-term heating capacity. A DC bias power source with a voltage range of 1–30 V was used to study the fabric Joule heating behaviour. Uniform heating and a subsequent steady temperature profile are observed. The PANI coated fabric could be used for sensing, joule-heating, and electromagnetic shielding applications in wearable electronics and advanced transport design. Highlights: Polyaniline-Cotton incorporation via in-situ oxidative polymerization. Achieved surface resistivity of 1.39 kΩ/cm. Fabric temperature reached 38 °C (within 30s) by applying a 15 V DC power supply. The textile material can be used as a responsive thermoregulatory interface.